Population of exciton-polaritons via luminescent sp3 defects in single-walled carbon nanotubes - Lüttgens, Jan; Berger, Felix J.; Zaumseil, Jana (ACS photonics, 2021)
Semiconducting single-walled carbon nanotubes (SWCNTs) are an interesting material for strong-light matter coupling due to their stable excitons, narrow emission in the near-infrared region, and high charge carrier mobilities. Furthermore, they have emerged as quantum light sources as a result of the controlled introduction of luminescent quantum defects (sp3 defects) with red-shifted transitions that enable single-photon emission. The complex photophysics of SWCNTs and the overall goal of polariton condensation pose the question of how exciton-polaritons are populated and how the process might be optimized. The contributions of possible relaxation processes, i.e., scattering with acoustic phonons, vibrationally assisted scattering, and radiative pumping, are investigated using angle-resolved reflectivity and time-resolved photoluminescence measurements on microcavities with a wide range of detunings. We show that the predominant population mechanism for SWCNT exciton-polaritons in planar microcavities is radiative pumping. Consequently, the limitation of polariton population due to the low photoluminescence quantum yield of nanotubes can be overcome by luminescent sp3 defects. Without changing the polariton branch structure, radiative pumping through these emissive defects leads to an up to 10-fold increase of the polariton population for detunings with a large photon fraction. Thus, the controlled and tunable functionalization of SWCNTs with sp3 defects presents a viable route toward bright and efficient polariton devices.
Published: December 9, 2020
Im Titel ist die Zahl "3" hochgestellt
Gesehen am 10.09.2021